Towards Cognitive Cities Advances in Cognitive Computing and its Application to the Governance of Large Urban Systems - Portmann, Edy; Finger, Matthias (Studies in Systems, Decision and Control,, 2016)
This book introduces the readers to the new concept of cognitive cities. It demonstrates why cities need to become cognitive and why therefore a concept of cognitive city is needed. It highlights the main building blocks of cognitive cities and illustrates the concept by various cases. Following a concise introductory chapter the book features nine chapters illustrating various aspects and dimensions of cognitive cities. The logic of its structure proceeds from more general considerations to more specific illustrations. All chapters offer a comprehensive view of the different research endeavours about cognitive cities and will help pave the way for this new and innovative approach to governing cities in the future. .